ANALISIS TINGKAT RESPON SISWA KELAS V TERHADAP TUGAS RUMAH PADA SEKOLAH YANG MENERAPKAN PROGRAM FULL DAY SCHOOL - Sidqi Aliyya, Lisana; Sukma Nugraha, Widdy; Koswara Adiredja, Rajji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The full-day school program was implemented as an effort to improve the quality of education by increasing students' learning time at school. This system provides opportunities for students to gain broader learning experiences, both in academic aspects and character development. However, the implementation of the full-day school program also raises questions about students' responses to homework (PR) after undergoing learning activities throughout the day at school. This study aims to determine the level of response of fifth-grade students to homework in schools that implement the full-day school program. This study uses a descriptive quantitative approach with a survey method. The study population was all fifth-grade students at one of the elementary schools in Garut, totaling 25 students, and all of them were used as research samples. The data collection instruments used were a Likert-scale questionnaire and interviews as supporting data. Data were analyzed using descriptive statistical techniques through the stages of editing, coding, scoring, and data tabulation. The results showed that the level of student response to homework was in the high category at 84% (22 students), the medium category at 16% (3 students), and there were no students in the low category. These results indicate that the majority of students have a positive response to homework despite following the full-day school system. These findings indicate that giving homework is acceptable to students as long as the assignments are appropriate for their abilities and relevant to the learning material.